[Collection of documents pertaining to opposition to increased excise taxes] - WALTER WOODSON (Tufts Archival Research Center, 2007)
Collection of documents pertaining to opposition to increased excise taxes. Lists groups to whom the Labor Management Committee will grant funds. Contains editorial from the American Farm Foundation applauding Clinton's broad idea but critizing his plan to raise tobacco taxes. Includes resolutions from two Ohio labor unions to oppose cigarette taxes. Covers American Agriculture meeting with White House representatives and meetings between tobacco farmers and members of the Congressional Black Caucus.